SENTRA HAK KEKAYAAN INTELEKTUAL ASPEK BUDAYA MUTU PERGURUAN TINGGI DI INDONESIA - Dr. Eka Priambodo, S.H., M.H (LP3M, 2022)
Universities produce many scientific works that can be valuable and must be protected, which so far have not been protected, with several cases, including plagiarism, not producing economic value, not being appreciated, and lack of accreditation assessment. For this reason, it is important to provide legal protection for the resulting Intellectual Property Rights so that they can be valuable and can guarantee the rights of researchers. However, not all universities provide facilities and facilitators for lecturers and students who produce scientific works, namely by not providing education, forums, and policies that assist in the registration of intellectual property rights. In addition, Intellectual Property Rights is one of the points in the assessment of credit scores for Lecturers. The problem in this study is how the role of the Intellectual Property Rights Center in universities and whether Intellectual Property Rights can be a point of quality culture at universities in Indonesia. Based on this description, the researcher intends to conduct a study entitled Center for Intellectual Property Rights Aspects of Quality Culture of Higher Education in Indonesia. The purpose of this study was to determine the need to establish a center for Intellectual Property Rights as a Higher Education Quality Culture. This study uses a normative juridical approach, namely by taking an inventory, reviewing, and analyzing and understanding the law as a set of regulations and positive norms in the applicable legal system. Protection of copyrighted works within universities is very important in order to improve the quality of research and community service, the HKI Center is one of the institutions that can encourage IPR behavior and become a Quality Culture in Higher Education and increase the assessment of college accreditation.